On the formation and annihilation of the singlet molecular metastables in an oxygen discharge. (13th July 2015) - Toneli, D A; Pessoa, R S; Roberto, M; Gudmundsson, J T
Abstract: We describe a volume averaged global model for an inductively coupled RF oxygen discharge that considers an extensive reaction set that includes the species: O2 (X ), O2 ( ), O2 ( ), O2 (A, A', ), O, O, O( 3 P), O( 1 D), O +, O −, O3, O, O, and electrons. We propose revised rate coefficients for some of the reactions and explore the densities of various species as a function of discharge pressure, in the pressure range 1–100 mTorr. We find that the O2 ( ) density can be lower than the O2 ( ) density in the pressure range from 2.5 to 80 mTorr. The relative reaction rates for formation and annihilation of O2 ( ) and O2 ( ) are evaluated and the most important reactions are indicated. The O − loss process is also studied. The results show that O2 ( ) has only a small contribution to the loss of the negative ion O −, while electron impact detachment is a very effective loss process at low pressure (<2 mTorr) and detachment by the oxygen atom O( 3 P) and the metastable singlet O2 ( ) are the most effective loss process up to roughly 50 mTorr where charge exchange becomes the most effective process for O − loss.